Efficient Covalent Bond Formation in Gas-Phase Peptide-Peptide Ion Complexes with the Photoleucine Stapler - Shaffer, Christopher J; Andrikopoulos, Prokopis C; Řezáč, Jan; Rulíšek, Lubomír; Tureček, František (Journal of the American Society for Mass Spectrometry, 2016)
Noncovalent complexes of hydrophobic peptides GLLLG and GLLLK with photoleucine (L*) tagged peptides G(L* n L m )K (n = 1,3, m = 2,0) were generated as singly charged ions in the gas phase and probed by photodissociation at 355 nm. Carbene intermediates produced by photodissociative loss of N2 from the L* diazirine rings underwent insertion into X-H bonds of the target peptide moiety, forming covalent adducts with yields reaching 30%. Gas-phase sequencing of the covalent adducts revealed preferred bond formation at the C-terminal residue of the target peptide. Site-selective carbene insertion was achieved by placing the L* residue in different positions along the photopeptide chain, and the residues in the target peptide undergoing carbene insertion were identified by gas-phase ion sequencing that was aided by specific (13)C labeling. Density functional theory calculations indicated that noncovalent binding to GL*L*L*K resulted in substantial changes of the (GLLLK + H)(+) ground state conformation. The peptide moieties in [GL*L*LK + GLLLK + H](+) ion complexes were held together by hydrogen bonds, whereas dispersion interactions of the nonpolar groups were only secondary in ground-state 0 K structures. Born-Oppenheimer molecular dynamics for 100 ps trajectories of several different conformers at the 310 K laboratory temperature showed that noncovalent complexes developed multiple, residue-specific contacts between the diazirine carbons and GLLLK residues. The calculations pointed to the substantial fluidity of the nonpolar side chains in the complexes. Diazirine photochemistry in combination with Born-Oppenheimer molecular dynamics is a promising tool for investigations of peptide-peptide ion interactions in the gas phase. Graphical Abstract ᅟ.
Keywords: Photolysis; simulace molekulární dynamiky; leucin; Born-Oppenheimer molecular dynamics; Molecular Dynamics Simulation; Leucine; vodíková vazba; fotolýza; Peptide–peptide ion complexes; plyny; molekulární modely; Models, Molecular; Gases; Photoleucine; Laser photodissociation; Diazirine chromophores; Peptides; peptidy; Diazomethane; ionty; Ions; Hydrogen Bonding; diazomethan